2020
DOI: 10.1016/j.xkme.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Group-Based Care in Adults and Adolescents With Hypertension and CKD: A Feasibility Study

Abstract: Rationale & Objective Group-based care provides an opportunity to increase patient access to providers without increasing physician time and is effective in the management of chronic diseases in the general population. This model of care has not been investigated in chronic kidney disease (CKD). Study Design Randomized controlled trial in adults (n = 50); observational study in adolescents (n = 10). Setting & Participants Adults and adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Nonsignificant improvements were reported in 90 domains across 14 studies. 28 , 29 , 30 , 35 , 36 , 39 , 42 , 44 , 45 , 47 , 54 , 58 , 78 , 79 , 88 , 90 No difference in QoL between intervention and control arms were reported for 3 domains across 3 studies, 47 , 49 , 58 whereas nonsignificant reductions in QoL after lifestyle interventions, compared with those of control, were reported in 17 domains across 10 studies. 36 , 43 , 44 , 45 , 47 , 49 , 54 , 58 , 78 , 79 , 88 No studies reported statistically significant reductions in QoL after lifestyle interventions, compared with those of the control.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Nonsignificant improvements were reported in 90 domains across 14 studies. 28 , 29 , 30 , 35 , 36 , 39 , 42 , 44 , 45 , 47 , 54 , 58 , 78 , 79 , 88 , 90 No difference in QoL between intervention and control arms were reported for 3 domains across 3 studies, 47 , 49 , 58 whereas nonsignificant reductions in QoL after lifestyle interventions, compared with those of control, were reported in 17 domains across 10 studies. 36 , 43 , 44 , 45 , 47 , 49 , 54 , 58 , 78 , 79 , 88 No studies reported statistically significant reductions in QoL after lifestyle interventions, compared with those of the control.…”
Section: Resultsmentioning
confidence: 98%
“…Dietary interventions were investigated in 24 studies, 46 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 with exercise interventions used in 23 studies. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 Eleven studies assessed interventions involving multiple components (eg, both diet and exercise), 16 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Johns et al .’s study, 31 10 adolescents (median age 18.0 years) underwent monthly group-based care sessions over 6 months. Sessions involved self-care activities (e.g.…”
Section: Bodymentioning
confidence: 99%
“…Furthermore, there have been limited efforts to implement interventions to increase physical activity behaviour, and those that have tried have had seemingly negligible effects. 30 , 31 In this context, it is important to note that drivers of inactivity are likely different across disease sub-groups (e.g. in KTx recipients, barriers include fear of injury, while in those on dialysis, a lack of time may be a greater hindrance), and these should be accounted for in the promotion of physical activity behaviour.…”
Section: Bodymentioning
confidence: 99%